Examining the Role of Social Media Marketing on Brand Love and Its Impact on Brand Centrality: The Study of Local Fashion Brands for the Millennials - Iin Mayasari; Handrix Chris Haryanto; Olivia Deliani Hutagaol; Adam Rizky Ramadhan; Iwan Amir (Journal of Indonesian Economy and Business, 2023)
Purpose: Local fashion brands are an important issue for millennial consumers. To create their love of local fashion brands, social media marketing is necessary. The study also examines brand love's effects on local fashion brands' centrality. This study also investigates brand love and centrality’s impact on the repurchase intention. Design/ Methodology/Approach: The data were taken using survey methods with questionnaires developed by previous researchers. A partial least squares regression was used to test the hypotheses. Findings: This study shows that social media marketing can create conditions for consumers to develop brand love, but brand love still needs to be able to develop brand centrality. This study also shows that although brand love has yet to create brand centrality, the concept of brand love can influence the repurchase intention. At the same time, brand centrality also affects the repurchase intention. Originality/value: This is the first study analyzing millennials’ brand love toward fashion clothing brands and the analysis of the influence of social media marketing on brand love and its impact on brand centrality.